Singlet fission in rubrene single crystal : direct observation by femtosecond pump–probe spectroscopy - Gurzadyan, Gagik G. (2013)
The excited state dynamics of rubrene in solution and in the single crystal were studied by femtosecond pump–probe spectroscopy under various excitation conditions. Singlet fission was demonstrated to play a predominant role in the excited state relaxation of the rubrene crystal in contrast to rubrene in solution. Upon 500 nm excitation, triplet excitons form on the picosecond time scale via fission from the lowest excited singlet state. Upon 250 nm excitation, fission from upper excited singlet states is observed within 200 fs.